Audit of Benzodiazepine and Z-Drugs Prescription in an Acute Inpatient Adult Psychiatric Unit in North Wales With the Aim of a Quality Improvement Project - Ashna Anil; Simran Bhupal; Sathyan Soundararajan; Chloe Turner; Asha Dhandapani (BJPsych Open)
Aims: This audit aims to assess the prescribing practices of benzodiazepines and hypnotics within the Heddfan inpatient psychiatric unit. These medications are effective in managing acute anxiety, agitation, and insomnia; however, they carry significant risks, including dependency, cognitive impairment, and an increased likelihood of falls.